2012
DOI: 10.1016/j.econlet.2012.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Price inflation and stock returns

Abstract: Working papers are in draft form. This working paper is distributed for purposes of comment and discussion only. Its contents should be considered to be preliminary and may not be reproduced without permission of the copyright holder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
1
9
0
1
Order By: Relevance
“…Lee (2010) found evidence that there was a negative relationship between inflation and stock returns during the post-war period while there was a positive relationship during the pre-war period. Furthermore, Oxman (2012) used data from 1966 to 2009 and separated the sample into two periods, i.e. 1966-1983 and 1984-2009 and observed that there was a rapid price increase in the 1970s that was moderated significantly after the early 1980s but did not appear to have any effect after 1983.…”
Section: Impact Of Macroeconomic Factors On Jakarta Islamic Indexmentioning
confidence: 99%
“…Lee (2010) found evidence that there was a negative relationship between inflation and stock returns during the post-war period while there was a positive relationship during the pre-war period. Furthermore, Oxman (2012) used data from 1966 to 2009 and separated the sample into two periods, i.e. 1966-1983 and 1984-2009 and observed that there was a rapid price increase in the 1970s that was moderated significantly after the early 1980s but did not appear to have any effect after 1983.…”
Section: Impact Of Macroeconomic Factors On Jakarta Islamic Indexmentioning
confidence: 99%
“…A well-known concept of an increase in the general level of prices, that is inflation, is typically measured through Consumer Price Index (CPI) (Oxman, 2012). However, it is not only the measure of inflation, as there may be different variables affecting inflation.…”
Section: Conceptual Clarification 21 Inflationmentioning
confidence: 99%
“…On that account, the rise in current and expected inflation should raise the nominal dividend payments. Accordingly, Oxman (2012) justified that the discount rate should be calculated by the returns rate which the investors had expected to gain as dividend yield on the stock. For that reason, the rise in inflation expectations should have a positive relationship with the flow of nominal dividend payments for stock.…”
Section: The Effect Of Inflation Rate On Stock Returnsmentioning
confidence: 99%
“…Ayrıca, sanayi üretim endeksi, döviz kuru, TÜFE, para arzı, altın fiyatları değişkenlerindeki değişimin İMKB 100 Endeksini pozitif ve anlamlı bir şekilde etkilediği; faiz oranı ve dış ticaret dengesi değişkenlerindeki değişimin ise, negatif ve anlamlı bir şekilde etkilediği belirlenmiştir. Oxman (2012), fiyat enflasyonu ve pay getirilerini S&P 500 Endeksi verileri üzerinden VAR metodu kullanarak incelemiştir. Çalışmadan ulaşılan sonuç, İkinci Dünya Savaşı'ndan sonra fiyat enflasyonu ve pay getirilerinin negatif olarak ilişkilendirilmesinin, çalışmalarda uygulanan modellerin spesifikasyonuna bağlı olduğu şeklindedir.…”
Section: Li̇teratürunclassified